Analisis Tingkat Pelayanan ( Level of service ) Ruas jalan Wolter Monginsidi Kecamatan Girian Kota Bitung - Rizki Teppie; Jeffrey A. Delarue; Toar U. Y. Pangkey (Sustainable Construction (SUSCON), 2023)
The Wolter Monginsidi road section is one of the main access points to downtown Bitung. At present this road section often experiences traffic jams during peak hours caused by community activities at the Girian Weru traditional market and activities at SMP Negeri 1 Bitung city and several shops on the side of the road. This study aims to analyze the Level of Service (Level Of Service). The method used in analyzing the data was the Indonesian Road Capacity Manual 1997. The side friction survey was carried out for two days, Monday and Friday, while the traffic survey was carried out for six days, Monday to Sunday. After analyzing the data, it was obtained that the road capacity was 1848 SMP/hour, the side resistance class was in the very high category (VH) where the total side resistance was 900, namely 1077 incidents per hour, the peak traffic flow was 1488 SMP/hour, the average speed of the vehicle the highest light is 17 km/hour and the lowest is 11 km/hour, and the Degree of Saturation value is 0.80, the Service Level for the Wolter Monginsidi road section in Bitung city is categorized at level D. The recommended recommendations are maximizing the width of the shoulder of the road by 1 meter, diverting trucks containers use the toll road as access to and from the port and widen the road body by 1 meter.